2015
DOI: 10.1089/biores.2015.0002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteogenic Differentiation in Human Mesenchymal Stem Cells by Crosstalk with Osteoblasts

Abstract: Natural bone healing following fractures is initiated by osteoblasts (OBs) and mesenchymal stem cells (MSCs), a cell combination with possible potential in tissue engineering techniques for bony defects. The aim of the study was to investigate MSC/OB-crosstalk, in order to determine optimal cell culture conditions for osteogenic differentiation. Human OBs and MSCs interactions were investigated in an in vitro trans-well co-culture study over a time period of 28 days. Calcification was determined by optical den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
4
17
0
1
Order By: Relevance
“…SOX9/RUNX2 ratio, chondrogenesis‐conducive aggregate culture, and osteogenesis inductive P21‐RUNX2‐8R can likely promote osteoclast formation needed for osteochondral differentiation. Similar gene expression profile was observed in the works of Schagemann et al and Glueck et al, where TGFβ (present in chondrogenesis medium) enhances chondrocyte differentiation, osteoblast maturation, and osteoclast maturation .…”
Section: Resultssupporting
confidence: 87%
“…SOX9/RUNX2 ratio, chondrogenesis‐conducive aggregate culture, and osteogenesis inductive P21‐RUNX2‐8R can likely promote osteoclast formation needed for osteochondral differentiation. Similar gene expression profile was observed in the works of Schagemann et al and Glueck et al, where TGFβ (present in chondrogenesis medium) enhances chondrocyte differentiation, osteoblast maturation, and osteoclast maturation .…”
Section: Resultssupporting
confidence: 87%
“…Β-glycerophosphate which is an integral component of osteogenic differentiation media to provide a phosphate source for the mineralizing osteoblasts, is regarded as hypertrophy promoting reagent for chondrocytes [ 27 ]. The main component of chondrogenic differentiation medium, TGF-β, was shown to cause a downregulation of ALP expression [ 28 ], which was also found in our study for MSC seeded in scaffolds from mineralized salmon collagen ( Figure 4 ). Based on these results we propose an osteochondral medium containing a reduced amount of TGF-β (5 ng/mL), no FCS, high glucose content, bovine serum albumin, as well as the factors stimulating both osteogenic and chondrogenic differentiation: dexamethasone and ascorbic acid-2-phosphate.…”
Section: Discussionsupporting
confidence: 83%
“…In conclusion it is known that local and systemic concentrations of different osteogenic cytokines increase during physiological fracture healing, in particular sufficient serum concentrations of TGF-ß have been shown to be pivotal to fracture healing [ 36 ]. It has been reported that TGF-ß and BMPs are capable of inducing each others expressions [ 33 , 34 ], however patients with failed bone healing are known to have impaired local BMP concentration, furthermore the current study showed that the concentration of TGF-ß in concerned patients is decreased during the initial 12 months; indicating that BMP-7 and TGF-ß have to be present in fracture healing in a sufficient concentration [ 37 ]. Our results show that local application of BMP-7 serves as a substitution of impaired BMP-7 levels in non-union patients and thereby modulating the microenviroment in the fracture gap and promoting bone regeneration.…”
Section: Discussionmentioning
confidence: 65%